Did Padre Damaso rape Pia Alba? reticence, revelation, and revolution in José Rizal's novels - Hau, Caroline Sy (Quezon City Ateneo de Manila University, 2017)
"This article revisits the debate in 2010 among Philippine Daily Inquirer columnists over the question of whether or not, in José Rizal's novel Noli Me Tangere, Padre Damaso "raped" Maria Clara's mother, Pia Alba, a debate inspired by the Reproductive Health (RH) Bill. The article examine how Rizal employs rhetorical strategies of reticence and revelation along with literary onomastics and allusions in his two novels to create meanings and associations that open his novels to multiple, even competing, interpretations. Such ambiguity reveals the artistic, intellectual, and political stakes of interpretation, which involves not only the struggle for understanding and struggle over meaning, but also the struggle to make, unmake, and remake community."
Keywords: Rizal, José; Novels; Noli me tángere; Crowds and people